Meta-Analysis and Systematic Review of the Association between a Hypoactive NCF1 Variant and Various Autoimmune Diseases - Liang Zhang; Jacqueline Wax; Renliang Huang; Frank Petersen; Xinhua Yu (MDPI AG, 2022)
Genetic association studies have discovered the GTF2I-NCF1 intergenic region as a strong susceptibility locus for multiple autoimmune disorders, with the missense mutation NCF1 rs201802880 as the causal polymorphism. In this work, we aimed to perform a comprehensive meta-analysis of the association of the GTF2I-NCF1 locus with various autoimmune diseases and to provide a systemic review on potential mechanisms underlying the effect of the causal NCF1 risk variants. The frequencies of the two most extensively investigated polymorphisms within the locus, GTF2I rs117026326 and NCF1 rs201802880, vary remarkably across the world, with the highest frequencies in East Asian populations. Meta-analysis showed that the GTF2I-NCF1 locus is significantly associated with primary Sjögren's syndrome, systemic lupus erythematosus, systemic sclerosis, and neuromyelitis optica spectrum disorder. The causal NCF1 rs201802880 polymorphism leads to an amino acid substitution of p.Arg90His in the p47phox subunit of the phagocyte NADPH oxidase. The autoimmune disease risk His90 variant results in a reduced ROS production in phagocytes. Clinical and experimental evidence shows that the hypoactive His90 variant might contribute to the development of autoimmune disorders via multiple mechanisms, including impairing the clearance of apoptotic cells, regulating the mitochondria ROS-associated formation of neutrophil extracellular traps, promoting the activation and differentiation of autoreactive T cells, and enhancing type I IFN responses. In conclusion, the identification of the association of NCF1 with autoimmune disorders demonstrates that ROS is an essential regulator of immune tolerance and autoimmunity mediated disease manifestations.